New Bio-Ceramization Processes Applied to Vegetable Hierarchical Structures for Bone Regeneration: An Experimental Model in Sheep - Filardo, Giuseppe (Mary Ann Liebert, Inc., 2014)
Bone loss is still a major problem in orthopedics. The purpose of this experimental study is to evaluate the safety and regenerative potential of a new scaffold based on a bio-ceramization process for bone regeneration in long diaphyseal defects in a sheep model. The scaffold was obtained by transformation of wood pieces into porous biomorphic silicon carbide (BioSiC(®)). The process enabled the maintenance of the original wood microstructure, thus exhibiting hierarchically organized porosity and high mechanical strength. To improve cell adhesion and osseointegration, the external surface of the hollow cylinder was made more bioactive by electrodeposition of a uniform layer of collagen fibers that were mineralized with biomimetic hydroxyapatite, whereas the internal part was filled with a bio-hybrid HA/collagen composite. The final scaffold was then implanted in the metatarsus of 15 crossbred (Merinos-Sarda) adult sheep, divided into 3 groups: scaffold alone, scaffold with platelet-rich plasma (PRP) augmentation, and scaffold with bone marrow stromal cells (BMSCs) added during implantation. Radiological analysis was performed at 4, 8, 12 weeks, and 4 months, when animals were sacrificed for the final radiological, histological, and histomorphometric evaluation. In all tested treatments, these analyses highlighted the presence of newly formed bone at the bone scaffolds' interface. Although a lack of substantial effect of PRP was demonstrated, the scaffold+BMSC augmentation showed the highest value of bone-to-implant contact and new bone growth inside the scaffold. The findings of this study suggest the potential of bio-ceramization processes applied to vegetable hierarchical structures for the production of wood-derived bone scaffolds, and document a suitable augmentation procedure in enhancing bone regeneration, particularly when combined with BMSCs.